AKULTURASI PENDIDIKAN AGAMA ISLAM DAN TRADISI NYADRAN DI DESA TUNGKULREJO, KECAMATAN PADAS, KABUPATEN NGAWI - Imam, Indah Fitri Sri Wulandari; Oktaviadina Astiari; Muh Tajab; Nuraini (TARBAWI:Journal on Islamic Education, 2024)
Nyadran is a symbol between ancestors, nature and each other. This is a ritual pattern that integrates native culture and Islamic educational values. Therefore, it is not surprising that the Nyadran tradition is still associated with the animist culture of Buddhist and Hindu teachings, then assimilated by the Islamic values taught by the Wali Songo. In addition, this research examines how acculturation and the impact of the Nyadran tradition have on the values of Islamic religious education. A qualitative research approach was used to answer the research questions. This research was conducted in Tungkulrejo Village, Padas District, Ngawi. Observations and in-depth interviews were used to collect data. The results of this research show that the acculturation of Islamic religious education and Nyadran culture is an integrated relationship in community life. Nyadran is a social form of society, unity and solidarity are the main patterns of this culture.